The influence of teaching motivations on student engagement in an online learning environment in China - Li, Qi; Jiang, Qiang; Liang, Jyh-Chong; Pan, Xingzhu; Zhao, Wei (Australasian Journal of Educational Technology, 2022)
Given the importance of student engagement for educational success, it is essential to explore how teachers can stimulate student engagement in online learning environment. However, relatively little research drawing from self-determination theory has examined the links between teaching motivations and student engagement. To this end, this study was conducted to survey 414 Chinese college students’ perceptions of teaching motivations, their own intrinsic and extrinsic motivations during the learning process, as well as their engagement with online learning. The findings indicated that the survey had satisfactory validity and internal consistency. Structural equation model revealed the interrelationships between autonomy-supportive teaching motivations, controlling teaching motivations, student intrinsic and extrinsic motivations, and student engagement. The results showed that in online learning environments, autonomy-supportive teaching motivations and student intrinsic motivation were positively related to student engagement. Unexpectedly, controlling teaching motivations and student extrinsic motivation had no significant effect on student engagement. Moreover, the mediating effects of student intrinsic motivation including perceived autonomy, competence, and relatedness offered a deeper understanding of the association between autonomy-supportive teaching motivations and student engagement. The main findings and practical implications together are discussed in depth. Implications for practice or policy: Teachers could adopt autonomy-supportive teaching strategies and stimulate students’ intrinsic motivation as they have shown to be positive factors for student engagement. Developers and educators could enhance student engagement through nurturing inner motivational resources in online learning environment. Researchers could verify more factors that influence student engagement and clarify how they could be manipulated in future studies.